Fekalotorax, gangréna a ztráta bránice. Kazuistika - Hoch, J; Pelichovská, M; Janík, V (Rozhledy v chirurgii, 2004)
Both stercoral peritonitis and pyothorax are rare but until nowadays threatening conditions. The presence of stool in the pleural cavity represents a curiosity, the gangrene and loss of the diaphragma is eminently rare. All above mentioned conditions occurred at the same time in the patient operated on for diffuse peritonitis after diverticular perforation of sigmoid. Surgery rescued peritoneal and pleural cavity. The absent diaphragma was replaced by mesh prosthesis, due to late intraabdominal complications the mesh was explantated. The patient survived and healed after repeated surgeries and long-lasting highly intensive therapy. Thanks to dislocation of viscera and adhaesive obliteration of the site of missing diaphragma left lung remained inflated and functional. The complication after 1 year--gastrobronchial fistula--was healed by left-sided pneumonectomy and suturing of the stomach.
Keywords: Peritonitis; Diaphragm; gangréna; Middle Aged; nekróza; mužské pohlaví; Gangrene; bránice; Necrosis; Humans; perforace střeva; divertikulitida tlustého střeva; peritonitida; Intestinal Perforation; Diverticulitis, Colonic; lidé; Male; lidé středního věku